Interview with Baltazar Ojea. Universities should assume their transformative role in society - Cuevas Gómez, Martha Elena (Emerging Trends in Education, 2022)
Interview with Baltazar Ojea,  Executive Director of URSULA (Unión de Responsabilidad Social Universitaria Latinoamericana).